The future of urban freight transport. Shifting the cities role from observation to operative steering. - Otte, Thomas; Fenollar Solvay, Alexia; Meisen, Tobias (My University, 2020)
Urban freight transport is characterised by an increasing frequency of shipments into urbanspaces. These shipments are carried out by a variety of freight carriers that operate independently and keep their operative information within their organisations. However, an unfortunate chaining of independent shipment operations affects the urban transportation network negatively. Establishing a data-based cooperation between these companies promises benefits for both the companies and the overall transportation network. In this context, an impartial and fair mediator is needed to bring together the data of each actor at a central point in order to steer the urban freight transport from a system perspective.This paper lays the fundament to prepare cities for taking over this responsible task. By creating a data foundation for the operative steering of the urban freight transport system, it contributes to national and supranationa objectives regarding the sustainable development and a worldwide pioneering role for Europe.
Keywords: Stadtverkehr; Frachtverkehr; Güterverkehr; Lieferverkehr; Stadtlogistik; Verkehrssteuerung; Smart City